Self‐Activated Cascade‐Responsive Sorafenib and USP22 shRNA Co‐Delivery System for Synergetic Hepatocellular Carcinoma Therapy. Issue 5 (15th January 2021) - Xu, Shengjun; Ling, Sunbin; Shan, Qiaonan; Ye, Qianwei; Zhan, Qifan; Jiang, Guangjiang; Zhuo, Jianyong; Pan, Binhua; Wen, Xue; Feng, Tingting; Lu, Haohao; Wei, Xuyong; et al.
Abstract: Resistance to sorafenib severely hinders its effectiveness against hepatocellular carcinoma (HCC). Cancer stemness is closely connected with resistance to sorafenib. Methods for reversing the cancer stemness remains one of the largest concerns in research and the lack of such methods obstructs current HCC therapeutics. Ubiquitin‐specific protease 22 (USP22) is reported to play a pivotal role in HCC stemness and multidrug resistance (MDR). Herein, a galactose‐decorated lipopolyplex (Gal‐SLP) is developed as an HCC‐targeting self‐activated cascade‐responsive nanoplatform to co‐delivery sorafenib and USP22 shRNA (shUSP22) for synergetic HCC therapy. Sorafenib, entrapped in the Gal‐SLPs, induced a reactive oxygen species (ROS) cascade and triggered rapid shUSP22 release. Thus, Gal‐SLPs dramatically suppressed the expression of USP22. The downregulation of USP22 suppresses multidrug resistance‐associated protein 1 (MRP1) to induce intracellular sorafenib accumulation and hampers glycolysis of HCC cells. As a result, Gal‐SLPs efficiently inhibit the viability, proliferation, and colony formation of HCC cells. A sorafenib‐insensitive patient‐derived xenograft (PDX) model is established and adopted to evaluate in vivo antitumor effect of Gal‐SLPs. Gal‐SLPs exhibit potent antitumor efficiency and biosafety. Therefore, Gal‐SLPs are expected to have great potential in the clinical treatment of HCC. Abstract : A galactose‐decorated lipopolyplex (Gal‐SLP) is developed as a hepatocellular carcinoma (HCC)‐targeting self‐activated cascade‐responsive nanoplatform to co‐deliver sorafenib and USP22 shRNA (shUSP22) for synergetic HCC therapy. Gal‐SLP exhibited a trio synergetic effect and achieved potent antitumor efficiency against a sorafenib‐insensitive patient‐derived xenograft.